Rosemary's baby - Castle, William; Polanski, Roman; Farrow, Mia, 1945-; Cassavetes, John, 1929-1989; Gordon, Ruth, 1896-1985; Blackmer, Sidney, 1895-1973; Levin, Ira, 1929-2007.; Paramount Home Entertainment (Firm) (Hollywood, CA Paramount, 1968)
Based on Ira Levin's bestselling novel, a young mother-to-be grows increasingly suspicious that her overfriendly elderly neighbors and self-involved actor husband are hatching a satanic plot against her and her baby.
Title from sell sheet.
From the novel by Ira Levin.
Originally released as a motion picture in 1968.
Wide screen.
Special features: Exclusive retrospective interviews; making of featurette.
Mia Farrow, John Cassavetes, Ruth Gordon, Sidney Blackmer.
Keywords: Satanism -- Drama; Demoniac possession -- Drama; Pregnancy -- Drama; Drama; Feature films; Horror films; Video recordings for the hearing impaired